Usability Analysis of The Bos Reporting Web Application Using The Sus Method - Ikrar Nusa Bhakti; Sucipto; Muhammad Najibulloh Muzaki (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
The e-BOS application is a web-based reporting system for managing School Operational Assistance (BOS) funds used by school operators to digitally report financial data. However, during implementation, various issues related to navigation, clarity of workflow, and reporting efficiency were reported by operators in Kertosono, Patianrowo, Baron, and Ngronggot Districts. These problems indicate that the application’s usability may not be optimal, thus requiring a systematic evaluation to assess user acceptance and application effectiveness. This study aims to evaluate the usability level of the e-BOS web-based reporting system managed by the Education Office of Nganjuk Regency. The research focuses on user experience among BOS operators in four districts using the System Usability Scale (SUS) method. A questionnaire consisting of 10 statements was distributed to 100 respondents. The collected data were analyzed using SUS scoring calculation, standard score interpretation, usability acceptability classification, and Net Promoter Score (NPS) categorization. The results show that the e-BOS application achieved an average SUS score of 56.8, categorized as Grade F (Worst Imaginable) and classified as Not Acceptable. Based on NPS, the score falls into the Detractor category, indicating that most users are unwilling to recommend the application to others. The study concludes that the e-BOS system has not met an adequate usability level and requires significant improvement, particularly in interface design, workflow simplification, and user guidance resources. This research is limited to four districts; thus, future studies are recommended to expand the sample coverage and compare usability performance after system improvements.